2018
DOI: 10.1175/jtech-d-18-0057.1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Inversion of Surface Ocean Kinematics from Sea Surface Temperature Observations

Abstract: The sea surface temperature (SST) record provides a unique view of the surface ocean at high spatiotemporal resolution and holds useful information on the kinematics underlying the SST variability. To access this information, we develop a new local matrix inversion method that allows us to quantify the evolution of a given SST perturbation with a response function and to estimate velocity, diffusivity, and decay fields associated with it. The matrix inversion makes use of the stochastic climate model paradigm—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…To this end we provide a global, spatially varying, empirical estimate of the magnitude of the diffusion tensor and its dependence on the spatial scale at the ocean surface. We base our estimates on satellite observations, a tracer simulation, and a recently developed statistical inversion methodology (MicroInverse; Nummelin et al 2018; see also Jeffress and Haine 2014a,b). While this paper and its supplement introduces the MicroInverse method, we encourage the readers who are interested in understanding the method in detail to read Nummelin et al (2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end we provide a global, spatially varying, empirical estimate of the magnitude of the diffusion tensor and its dependence on the spatial scale at the ocean surface. We base our estimates on satellite observations, a tracer simulation, and a recently developed statistical inversion methodology (MicroInverse; Nummelin et al 2018; see also Jeffress and Haine 2014a,b). While this paper and its supplement introduces the MicroInverse method, we encourage the readers who are interested in understanding the method in detail to read Nummelin et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Observational and model-based evidence suggest that k varies in space both at the ocean surface (Shuckburgh et al 2009;Marshall et al 2006;Abernathey and Marshall 2013;Zhurbas et al 2014;Klocker and Abernathey 2014;Busecke et al 2017;Nummelin et al 2018) and at depth (Smith and Marshall 2009;Abernathey et al 2010;Vollmer and Eden 2013;Cole et al 2015;Roach et al 2018;Bachman et al 2020;Groeskamp et al 2020;Stanley et al 2020). Surface diffusivity also varies in time with the atmospheric forcing (Shuckburgh et al 2009;Busecke and Abernathey 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical estimation of stochastic models has a long history starting with ML and least squares estimates as a simplification; see Le Breton (1977) and DelSole and Yang (2010). In application to climate statistics, reviews can be found in DelSole and Hou (1999) and DelSole and Chang (2003) and comparisons in Mason and Mimmack (2002) and Nummelin et al (2018). From Penland (1989), the use of FDT approximations for the LIM to derive closed-form parameter estimation formulas makes this approach the method of choice in geoscience applications (Penland 1989;Penland and Sardeshmukh 1995;Nummelin et al 2018;Barnston et al 1999;Colman and Davey 2003), particularly over various autoregressive models (DelSole and Chang 2003;Penland et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In application to climate statistics, reviews can be found in DelSole and Hou (1999) and DelSole and Chang (2003) and comparisons in Mason and Mimmack (2002) and Nummelin et al (2018). From Penland (1989), the use of FDT approximations for the LIM to derive closed-form parameter estimation formulas makes this approach the method of choice in geoscience applications (Penland 1989;Penland and Sardeshmukh 1995;Nummelin et al 2018;Barnston et al 1999;Colman and Davey 2003), particularly over various autoregressive models (DelSole and Chang 2003;Penland et al 1993). Barnston et al (2012) compares LIMs and other physically and statistically based models in the International Research Institute for Climate and Society (IRI) ENSO prediction plume.…”
Section: Introductionmentioning
confidence: 99%